Treatment Option for Abernethy Malformation—Two Cases Report and Review of the Literature - Lin, Yuese; Li, Xuandi; Li, Shujuan; Ba, Hongjun; Wang, Huishen; Zhu, Ling (Frontiers in Pediatrics, 2020)
Background: Abernethy malformation is a rare vascular anomaly of the portal venous system, which is also known as congenital portosystemic shunts (CPSS). The clinical manifestations of this anomaly can be serious, including hepatopulmonary syndrome(HPS), which can lead to significant hypoxemia and cyanosis. Case Presentation: This study reports two cases of patients with Abernethy Malformation. Case 1 was a 6-year-old boy whose blood oxygen saturation was 78%. Case 2 was a 6-year-old girl who had a history of open heart surgery and residual cardiac left to right shunt, whose blood oxygen saturation was 83%. These two children had unexplained cyanosis and were diagnosed with pulmonary arteriovenous fistula by contrast echocardiography with agitated saline. A selective retrograde catheter angiography confirmed the presence of a portosystemic shunt. Case 1 was a type I Abernethy malformation and did not receive any specific treatment and could only wait for liver transplantation. Case 2 was with type II Abernethy and underwent transcatheter closure of the CPSS. A 20mm-diameter, 14mm-long Vascular Plug (SHSMA Inc, Shanghai, China) was used to occlude the shunt. Results: In case 1, the boy developed deteriorating cyanosis and dyspnea on exertion. In case 2, the exercise tolerance of the patient improved after shunt closure. During a follow-up of 3 years, her blood oxygen saturation increased from 83 to 98%. Conclusion: The results indicate that children with unexplained cyanosis require special attention since these patients may have Abernethy malformation, and part of them could be treated by transcatheter occlusion with a good outcome. The key to treatment is how it is diagnosed and carefully assessed.